Health Care Student Perceptions of Societal Vulnerability to Disasters in the Context of Population Aging. (25th July 2018) - Lucas, Peter; Annear, Michael; Harris, Wayne; Eyles, Helen; Rotheram, Auston
ABSTRACT: Objective: This paper reports on undergraduate health care students' perception of societal vulnerability to disasters in the context of population aging. Forecast increases in extreme weather events are likely to have a particularly devastating effect on older members of the community. Methods: Undergraduate paramedicine and nursing students were surveyed using the Perceptions of Ageing and Disaster Vulnerability Scale (PADVS) to determine their views on the risks posed to older members of the community by disasters. Data analysis included a comparison of subscales relating to isolation, health system readiness, declining function, and community inclusiveness. Results: Students reported a moderate level of concern about disaster vulnerability. Students who had previously completed another university degree reported significantly higher levels of concern than those without a prior degree. Australian students reported lower concern about societal vulnerability compared to a previously reported cohort of Japanese students. Conclusion: Our study suggests current education of future health care students does not promote adequate levels of awareness of the health-related challenges posed by disasters, particularly among older members of the community. Without addressing this gap in education, the risk of negative outcomes for both unprepared first responders and older members of the community is significant. ( Disaster Med Public Health Prep . 2019;13:449-455)